SISTEM PAKAR UNTUK KERUSAKAN PADA PRINTER DENGAN DELPHI 7 - Bagus Dwi Cahyono; Irwanto; Muhammad Iqbal Nugraha (Jurnal Teknik Informatika dan Teknologi Informasi, 2022)
An expert system is an artificial intelligence program that combines a knowledge base with an inference system which is part of a high-level specialization software that seeks to duplicate the function of an expert in a field of expertise. This system was created with the aim of solving certain problems by imitating the work of experts from a field. Currently handling printer damage takes a long time to repair because there are many other printers that must be repaired. This expert system application uses the forward chaining method and literature studies into the Delphi 7 application which is useful for diagnosing damage and providing solutions to be carried out according to the symptoms given.